2022
DOI: 10.1111/crj.13493
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness, nephrotoxicity, and therapeutic drug monitoring of polymyxin B in nosocomial pneumonia among critically ill patients

Abstract: Objectives We aimed to assess the effectiveness and nephrotoxicity of polymyxin B in critically ill patients with nosocomial pneumonia and to evaluate the utility of its therapeutic drug monitoring (TDM). Methods We retrospectively analyzed patients who received polymyxin B treatment for ≥48 h since the establishment of polymyxin B TDM in a 26‐bed tertiary referral intensive care unit. Univariate and multivariate analyses were conducted to assess the variables associated with polymyxin B effectiveness and neph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…These specific physiological features may cause changes in drug pharmacokinetic (PK), such as drug clearance and apparent volume of distribution, which lead to insufficient antibiotics concentrations in sites of infection and are associated with prolonged hospital stay and poor prognosis ( Udy et al, 2013 ). Previous PK/PD studies have shown that the rate of reaching the standard polymyxin B exposure AUC at a typical clinical dose is low, approximately 54.3% ( Ye et al, 2022 ) in critically ill patients. However, the exact causes have never been defined.…”
Section: Introductionmentioning
confidence: 99%
“…These specific physiological features may cause changes in drug pharmacokinetic (PK), such as drug clearance and apparent volume of distribution, which lead to insufficient antibiotics concentrations in sites of infection and are associated with prolonged hospital stay and poor prognosis ( Udy et al, 2013 ). Previous PK/PD studies have shown that the rate of reaching the standard polymyxin B exposure AUC at a typical clinical dose is low, approximately 54.3% ( Ye et al, 2022 ) in critically ill patients. However, the exact causes have never been defined.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we found that AUC ss,24 h of > 100 mg h/L was a good predictor of the probability of nephrotoxicity ( P = 0.001) [ 16 ]. Ye et al found that the therapeutic target of AUC ss,24 h (odds ratio [OR] = 13.15, P = 0.015) was independently associated with favorable clinical outcomes of polymyxin B treatment [ 17 ]. Some studies reported that maintaining a trough concentration (C 0h or C min ) of polymyxin B below 3.13 mg/L or peak concentration (C max ) of polymyxin B1 below 5.23 mg/L might help reduce the incidence of polymyxin B-related nephrotoxicity [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The sample sizes per study ranged from 11 to 4910 critically ill patients. This systematic review and meta-analysis included 3 parallel cohort studies that reported outcome measures associated with colistin and PMB use[ 62 , 76 , 80 ], 2 studies with colistin and PMB use[ 17 , 68 ], 75 studies with colistin use alone[ 16 , 18 - 40 , 42 - 57 , 59 - 61 , 64 - 67 , 70 - 75 , 78 , 81 , 83 - 99 , 101 - 102 , 104 ] and 9 studies with PMB use alone[ 41 , 58 , 63 , 69 , 77 , 79 , 82 , 100 , 103 ]. Regarding the geographical distribution, 35 studies were conducted in Europe, 31 in Asia, 6 in North America, 6 in South America and 4 in Africa.…”
Section: Resultsmentioning
confidence: 99%